1998
DOI: 10.1002/ana.410440506
|View full text |Cite
|
Sign up to set email alerts
|

The phenotypic spectrum of CADASIL: Clinical findings in 102 cases

Abstract: Cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL) is an increasingly recognized autosomal dominant disorder that leads to cerebrovascular manifestations in early adulthood. This study delineates the phenotypic spectrum and the natural history of the disease in 102 affected individuals from 29 families with biopsy-proven CADASIL. Recurrent ischemic episodes (transient ischemic attack [TIA] or stroke) were the most frequent presentation found in 71% of the cases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
533
1
27

Year Published

2000
2000
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 640 publications
(580 citation statements)
references
References 37 publications
13
533
1
27
Order By: Relevance
“…The disease is characterized by recurrent TIAs and strokes with progressive vascular dementia, migraine with aura, psychiatric disturbances, and pseudobulbar palsy (2)(3)(4). In 1996, Joutel et al reported Notch3 as the causative gene for CADASIL, and detected several point mutations (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…The disease is characterized by recurrent TIAs and strokes with progressive vascular dementia, migraine with aura, psychiatric disturbances, and pseudobulbar palsy (2)(3)(4). In 1996, Joutel et al reported Notch3 as the causative gene for CADASIL, and detected several point mutations (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…This adds to previous clinical and neuroimaging evidence indicating, that the Notch3 genotype has no major influence on the phenotype. 3,22 In conclusion we have found a number of new mutations including two small in-frame deletions. These deletions are relevant in that they substantiate the pivotal role of an odd number of cysteine residues within EGF-like repeat domains in the pathogenesis of CADASIL.…”
Section: Discussionmentioning
confidence: 69%
“…1 Affected individuals experience recurrent ischemic episodes with accumulating motor, sensory and cognitive deficits. 2,3 The majority of patients eventually become demented and additional manifestations have been reported including migraine (30-40%), psychiatric disturbance (30%) and epileptic seizures (10%). 2,3 Brain magnetic resonance imaging (MRI) displays diffuse white matter abnormalities and small cystic lesions suggestive of small infarcts.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations